2000
DOI: 10.1016/s0886-3350(00)00559-9
|View full text |Cite
|
Sign up to set email alerts
|

Corneal iron ring associated with iatrogenic keratectasia after myopic laser in situ keratomileusis

Abstract: A 23-year-old woman had bilateral myopic laser in situ keratomileusis (LASIK). Two months postoperatively, she reported decreased visual acuity. Biomicroscopic examination revealed a corneal epithelial iron ring around the central keratectasia on both corneas. The appearance of the ring pattern was similar to the iron deposits of the Fleischer ring of keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…Careful review of each manuscript provided 21 relevant reports containing the individual case data presented here. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] We included all available data from each individual eye reported. Publications containing summary statistics, or ectasia from other procedures-photorefractive keratectomy, hyperopic LASIK, and radial keratotomy-were not included in this analysis.…”
Section: Ectasia Casesmentioning
confidence: 99%
“…Careful review of each manuscript provided 21 relevant reports containing the individual case data presented here. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] We included all available data from each individual eye reported. Publications containing summary statistics, or ectasia from other procedures-photorefractive keratectomy, hyperopic LASIK, and radial keratotomy-were not included in this analysis.…”
Section: Ectasia Casesmentioning
confidence: 99%
“…Despite the availability of such information, ectasia remains unpredictable. An analysis of the published cases of ectasia after LASIK 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] found that with most ectasias, progressive thinning of the cornea combined with central or inferior steepening results in a progressively increasing myopic refractive error and decrease in vision.…”
mentioning
confidence: 99%
“…1 Recently, several cases of iatrogenic keratectasia have been documented after excimer laser photorefractive keratectomy (PRK) and laser in situ keratomileusis (LASIK). [2][3][4][5][6][7][8][9][10][11][12][13][14] Thus, it is of clinical importance quantitatively and longitudinally to evaluate the influence of excimer laser surgery on the geometry of the cornea. In addition, forward shift of the cornea can affect refractive stability after corneal refractive surgery.…”
mentioning
confidence: 99%